Iodine supplementation by women of childbearing potential and in pregnancies - analysis of knowledge among students - Wójcik-Grudzień, Justyna; Ozga-Stachurska, Alicja; Pawłowska, Paulina; Rozenbajgier, Martyna (Journal of Education, Health and Sport, 2022)
Introduction Iodine is necessary for the proper production of triiodothyronine and thyroxine, which affect the development and proper functioning of the body. Thyroid hormones are involved in the transformation of proteins, fats, carbohydrates and vitamins, and also regulate the processes of cell growth and maturation. Iodine deficiency during pregnancy has many consequences for the fetus and newborn, some of them an increased risk of miscarriage, stillbirth, birth defects or abnormal mental development. Iodine deficiency through lack of supplementation or deficiency in the daily diet, as well as the consumption of an excess amount of this microelement, may be associated with serious and irreversible consequences affecting the development and further functioning of the fetus. Aim of the study Presentation of the impact of iodine supplementation in reproductive age and pregnancy on fetal development and students' knowledge of the need for this supplementation. Materials and method A survey of 404 students. The results were compared with the current scientific literature. Statistical analysis was performed using Microsoft Excel. Results In the study group, almost every third student believed that current recommendations recommend that women planning pregnancy should take iodine preparations. Every tenth student gave the correct dose of recommended supplementation of the microelement in question. Conclusions Research shows that more than half of students are not aware of the need to supplement iodine at the reproductive age. The data indicate that young people should be made aware of the need for iodine supplementation.